2022 American College of Rheumatology Guideline for Vaccinations in Patients With Rheumatic and Musculoskeletal Diseases. Issue 3 (4th January 2023) - Bass, Anne R.; Chakravarty, Eliza; Akl, Elie A.; Bingham, Clifton O.; Calabrese, Leonard; Cappelli, Laura C.; Johnson, Sindhu R.; Imundo, Lisa F.; Winthrop, Kevin L.; Arasaratnam, Reuben J.; Baden, Lindsey R.; Berard, Roberta; et al.
Abstract : Objective: To provide evidence‐based recommendations on the use of vaccinations in children and adults with rheumatic and musculoskeletal diseases (RMDs). Methods: This guideline follows American College of Rheumatology (ACR) policy guiding management of conflicts of interest and disclosures and the ACR guideline development process, which includes the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. It also adheres to the Appraisal of Guidelines for Research and Evaluation (AGREE) criteria. A core leadership team consisting of adult and pediatric rheumatologists and a guideline methodologist drafted clinical population, intervention, comparator, outcomes (PICO) questions. A review team performed a systematic literature review for the PICO questions, graded the quality of evidence, and produced an evidence report. An expert Voting Panel reviewed the evidence and formulated recommendations. The panel included adult and pediatric rheumatology providers, infectious diseases specialists, and patient representatives. Consensus required ≥70% agreement on both the direction and strength of each recommendation. Results: This guideline includes expanded indications for some vaccines in patients with RMDs, as well as guidance on whether to hold immunosuppressive medications or delay vaccination to maximize vaccine immunogenicity and efficacy. Safe approaches to the use of live attenuated vaccines in patients taking immunosuppressive medications are also addressed. Most recommendations are conditional and had low quality of supporting evidence. Conclusion: Application of these recommendations should consider patients' individual risk for vaccine‐preventable illness and for disease flares, particularly if immunosuppressive medications are held for vaccination. Shared decision‐making with patients is encouraged in clinical settings.